Transparent, Translucent, Opaque: Exploring the Dimensions of Power in Culturally Responsive Evaluation Contexts. (September 2019) - Stickl Haugen, Jaimie; Chouinard, Jill Anne
The concept of power is a complex and often intangible aspect of the evaluation process that is frequently a focal topic among the conceptual evaluation literature concerning collaborative or culturally responsive evaluation (CRE) contexts. Unfortunately, there remains a significant theory to practice gap as power is often rarely addressed or specifically identified in empirical practice. In the current article, the authors provide a comprehensive review of the empirical literature on CREs, with an emphasis on the manifestation of power in practice. The analysis of the literature selected for review leads to the development of a conceptual framework, which identifies intersecting power dynamics across the relational, political, discursive, and historical/temporal dimensions. The authors conclude with a research synthesis and implications for practice, including a discussion of practical ways that evaluators can begin with considerations of power rather than reflecting on the concept retrospectively.